The Presence of Classical Chinese Works in Libro de Sueños by J. L. Borges: Transmission and Rewriting - Lan, Zhang (Sinología hispánica. China Studies Review, 2024)
In this paper, we proceed to study and analyze the classical Chinese stories that appear in Borges’ anthology Libro de Sueños (Book of Dreams). Since Borges did not speak Chinese, we will try to discover the sources of these stories through his reviews of the translations into English and German of the Chinese canonical books, published in El Hogar, Sur and La Nación magazines in the 1930s and 1940s. We also aimed at examining the reason for the selection of these Chinese fictions, since the recurrent Borgesian themes (the mirror, the labyrinth, the nightmare, the double, the parallel universe, and the paradox of time) appear in these stories, as well as to discover the author’s identity; not only as a copyist, but also as an author, through the transmission and rewriting of these Chinese stories.